2020
DOI: 10.21009/jpeb.008.2.5
|View full text |Cite
|
Sign up to set email alerts
|

Personality, Gender, Culture, and Entrepreneurial Intentions of Undergraduate Student: Binary Logistic Regression

Abstract: In the last two decades, empirical studies on entrepreneurship had been increasing, especially the object of study of student entrepreneurial intention. The objective of this study was to examine the empirical evidence about significant factors and the most dominant factor (having the highest rank) influencing entrepreneurial intention of Islamic Shekh-Yusuf University students. This study used a descriptive quantitative approach that was a binary logistic regression analysis model with a sample of 382 respond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 28 publications
(49 reference statements)
0
4
0
Order By: Relevance
“…The feasibility test of the model in this study used the Hosmer and Lemeshow test. If the significance value is > 5 percent, then the model is feasible to use as a predictive tool (Mardisentosa et al, 2020). The results of the model analysis are shown in Table 4 below: Table 4…”
Section: Resultsmentioning
confidence: 99%
“…The feasibility test of the model in this study used the Hosmer and Lemeshow test. If the significance value is > 5 percent, then the model is feasible to use as a predictive tool (Mardisentosa et al, 2020). The results of the model analysis are shown in Table 4 below: Table 4…”
Section: Resultsmentioning
confidence: 99%
“…Entrepreneurial activity has largely been associated with cultures that are high in individualism, low in power distance, low in uncertainty avoidance and high in masculinity (Doe et al, 2016;Neira et al, 2017;Valliere, 2017), which is inconsistent with the characteristics found in Group 1. These links between Hofstede's (1980) cultural values and entrepreneurship have largely been mirrored in South Africa where high levels of individualism have been associated with entrepreneurial intention (Mardisetosa et al, 2020;Naqvi & Siddiqui, 2020). There are, however, opposing views that claim that moderate levels of individualism (as opposed to collectivism) will lead to greater levels of entrepreneurial activity (Bogatyreva et al, 2019;Iwu et al, 2016;Vershinina et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…However, culture and entrepreneurship are both elusive, multi-dimensional phenomena making comparative research complex (Doe et al, 2016;García-Cabrera & García-Soto, 2017;Naqvi & Siddiqui, 2020;Mardisetosa et al, 2020) and this could possibly explain the equivocal nature of the results exploring this link (Laskovaia et al, 2017). This conundrum is compounded in South Africa (Mothibi & Malebana, 2019) as research considering this link within the context of developing nations (Anlesinya et al, 2019;Ebewo et al, 2017;Neira et al, 2017;Shiri et al, 2017) and in particular the African continent (Iwu et al, 2016) is inadequate.…”
Section: Introductionmentioning
confidence: 99%
“…The research scheme concentrates on the quantitative form. Solving research objectives to answer hypotheses, where statistical results supported by IBM SPSS (Azhari et al, 2020;Mardisetosa et al, 2020). We collected cross-section through trusted sources, such as publications from the government of East Kalimantan Province (in this case, BPS and the Department of Communication and Information).…”
Section: Methodsmentioning
confidence: 99%